CORRELATION BETWEEN CONTENT MARKETING AND CUSTOMER ENGAGEMENT IN ARCADE TOURISM DESTINATIONS (CASE STUDY AT INSTAGRAM ACCOUNT @INFODUFAN) - Siti Fatimah; Devi Suci Lastari; Riyandi Riyandi; Abdul Yusuf (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
The ubiquitous utilization of the internet for marketing purposes on social media platforms has emerged as a remarkable phenomenon. The purpose of this study was to investigate the correlation between content marketing and consumer engagement, as well as to assess the strength of this correlation. The study population consisted of Instagram followers @infodufan. The research employed a quantitative methodology and included a sample size of 64 respondents. The data collection technique employs a questionnaire administered through Google Form. Subsequently, the obtained results are examined by correlation analysis. The research findings indicate a substantial correlation between content marketing and customer engagement at Dunia Fantasi. The Pearson association coefficient is 0.707, indicating a relatively significant positive association.